Changes in genetic variances and heritabilities in an early white maize population following S1 selection for grain yield, Striga resistance and drought tolerance - Badu-Apraku, Baffour; Oyekunle, M.; Talabi, A.O.; Annor, B.; Akaogu, I.C. (Cambridge University Press, 2017)
Drought is a major constraint to maize production in West and Central Africa (WCA). Assessment of genetic gain from S1 recurrent selection under drought is crucial for the development of drought tolerance breeding strategies. In an early white population, 60 S1 families each derived from the base population and three cycles of selection were evaluated under drought and well-watered conditions at two locations in Nigeria for 2 years to determine genetic variability, gains from selection and predict response to selection for grain yield and other traits. Genetic variances generally decreased for yield and other traits in advanced cycles under drought and well-watered conditions except yield and ear height under well-watered conditions. Similarly, heritabilities for yield and other traits decreased in advanced cycles under drought but increased in advanced cycles under well-watered conditions. Realized gain for yield was 0·291 t/ha, corresponding to 30·5% per cycle under drought and 0·352 kg/ha with a corresponding gain of 16·7% per cycle under well-watered conditions. Predicted gain based on C3 was 0·282 and 0·583 t/ha under drought and well-watered conditions. Low genetic variances, heritabilities and predicted gain for yield and other traits suggested a need to introgress drought tolerance genes into the population.